Mixed blessings - Steel, Danielle (Dell Pub., 1993)
After the wedding of Diana Goode and Andrew Douglas, Diana teases that they will make a baby on their honeymoon. But long afterward, she is still not pregnant. As Diana and Andrew wait out each month only to be bitterly disappointed, they are forced to question just how much they are willing to go through to have a baby. Charlie Winwood dreams of a house filled with children ...